Village Community Participation Model in Village Funds Management to Exteriorize the Accountability - Susilowati, N; Herdiani, A; Widhiastuti, R (KnE Social Sciences, 2018)
Villages are given a great opportunity to manage their own governance and to develop the infrastructure to enhance the welfare and life quality of their communities. In 2015 all villages in Indonesia have received village funds from State Budget (APBN). Village funds management needs the community involvement. However, most villagers are apathetic. The interview results with three stakeholders related to the management of village funds (village heads and the officials, the cadre of village and district community empowerment (KPMD) located in Semarang Regency reveal that the apathy of the village community is due to the community’s trust to the village head and the officials. In fact, the advice and involvement of village communities plays important roles in realizing good village governance. The involvement of village community in carrying out village activities can be trough community groups coordinated by each lurah, so thay the amount of village funds used for village activities can be clearly known by the community. In additional, good communication between village officials, communities, and sub-district heads can enhance the village budget absorption (APBDes). In other words, citizen control, delegated control, and partnership are considered in the management of village funds, which will exteriorize an accountability when all functions work approprietely. Keywords: citizen control, delegated control, partnership, village funds management, and accountability